Dopady zavedení eura na hospodaření firmy - Bergová, Hana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Cíl předkládané diplomové práce spočívá v identifikaci vlivů zavedení eura na hospodaření firmy Jihomoravská armaturka spol. s.r.o., z hlediska pozitivních a negativních stránek této změny. Literární rešerše se zabývá cestou ke společné měně v rámci historického vývoje HMU, popisem jednotlivých konvergenčních kritérií a harmonogramem zavedení eura v Česku. Následuje zhodnocení domácího podnikatelského sektoru a teoreticky rozebrané dopady eura bezprostředně na něj působící. Východiska literární části jsou aplikována na vybraný podnik v analýze jeho současného situace, spolu s určením celkového vlivu evropské měny. Závěr se věnuje doporučení a návrhů pro společnost do budoucnosti a v přípravném procesu zavádění eura.

Aim of the thesis is effects identification of the euro implementation on the company Jihomoravská armaturka Ltd.. and in terms positive and negative aspects of this change. Literature review deals with the way the common currency within the historical development of the EMU, the description of the convergence criteria and timetable for the introduction of the euro in Czech. Followed by evaluation of the domestic business sector and theoretically discussed the impact of the euro immediately acting on it. Basis of literature are applied to the selected firm in the analysis of the current situation, together with the determination of the overall impact of the European currency. The conclusion is devoted to recommendations and suggestions for the company to the future and in the preparatory process of the introduction of the euro.
Impact of Euro Implementation on Corporation Finance
Keywords: Eurozóna; Maastrichtská kritéria; Euro; Podnikatelský sektor; Přínosy a náklady; Strategický plán zavedení eura; Eurozone; Maastricht criteria; Euro; Business; Benefits and Costs; Strategic plan for the introduction of the euro